2015
DOI: 10.2147/ijn.s76134
|View full text |Cite
|
Sign up to set email alerts
|

Cell type-specific response to high intracellular loading of polyacrylic acid-coated magnetic nanoparticles

Abstract: Magnetic nanoparticles (NPs) are a special type of NP with a ferromagnetic, electron-dense core that enables several applications such as cell tracking, hyperthermia, and magnetic separation, as well as multimodality. So far, superparamagnetic iron oxide NPs (SPIONs) are the only clinically approved type of metal oxide NPs, but cobalt ferrite NPs have properties suitable for biomedical applications as well. In this study, we analyzed the cellular responses to magnetic cobalt ferrite NPs coated with polyacrylic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…There was almost complete absence of apolipoproteins in the corona of PAA NPs, with the exception of apolipoprotein A-I found in the corona of NPs dispersed in NaCl. Although there are some implications that apolipoprotein A-I is connected to bioaccumulation of NPs in cells [7] our PAA NPs were shown to accumulate in different cell lines despite of the absence of this specific protein in their corona [38,53]. Again, dispersion media proved to be a relevant factor in determining the NPs protein corona composition.…”
Section: Discussionmentioning
confidence: 98%
“…There was almost complete absence of apolipoproteins in the corona of PAA NPs, with the exception of apolipoprotein A-I found in the corona of NPs dispersed in NaCl. Although there are some implications that apolipoprotein A-I is connected to bioaccumulation of NPs in cells [7] our PAA NPs were shown to accumulate in different cell lines despite of the absence of this specific protein in their corona [38,53]. Again, dispersion media proved to be a relevant factor in determining the NPs protein corona composition.…”
Section: Discussionmentioning
confidence: 98%
“…In general, aggregated industrial SiO 2 induced small toxic effects only at extremely high concentration, while relatively stable TiO 2 and magnetic PAA NPs that could be internalized had several effects also at moderate concentrations. The short-term exposure (96 h) of L6 cells to TiO 2 induced a significant decrease in viability, and the highest concentration of PAA NPs induced a drop in L6 cell viability (statistically not significant) similarly as already observed on primary human myoblasts [ 56 ]. The drop in viability was probably due to membrane damage in case of magnetic PEI NPs, while for other NPs, there is little effect due to membrane damage (low percentage of PI positive cell), and effects are mostly on cell proliferation as already shown for magnetic PAA [ 56 , 67 ].…”
Section: Discussionmentioning
confidence: 54%
“…A continuous exposure simulated events of repeated or continuous exposure to NPs due to the presence of NPs in different consumer products or environmental pollution. We used four types of NPs: two biomedically relevant (magnetic PAA and PEI) NPs [ 8 , 56 , 57 , 58 , 59 ] and industrially relevant (SiO 2 and TiO 2 ) NPs as representative types of two very commonly used commercial NPs in various consumer products and materials. We analyzed the effects of NPs on the cell viability, morphology, and ultrastructure on both cell models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In various studies, it was also shown that next to uptake efficiency of particles, the extent of the adverse effects could also be strongly cell type dependent. 78,99,121,122 Because of these findings there is a continued effort in trying to generate more stable particles and/or particles with an improved balance between core composition and coating. 77,114,[123][124][125] In our group, we made the observation that for a liposomal encapsulated gadolinium particle, adverse effects on cellular functionality was more directly associated with the liposomal capsule than with the chelated gadolinium molecules.…”
Section: Effects Of Nanoparticle Compositionmentioning
confidence: 99%